Des territoires sans nom peuvent-ils être sans qualité ? Réflexions sur les modifications de la carte administrative chilienne - Anne-Laure Amilhat Szary (L'Espace Politique)
During years, democracy in Chile has been criticized for its lack of democratic representativeness. Then in two points of the country, the extreme north on one side (First Region called Tarapacá Region) and the south on the other side (Tenth Region of The Lakes), regionalism has taken a separatist trend: previous provinces, which importance had long been undermined by their surrounding regions, have claimed their independence. They have won the latter in 2007, after a very quick political arbitration, allowing in a few years what had long seemed impossible: the modification of the administrative map of the country established during the dictatorship years. When it comes to first balances, the impact of this change appears more profound than had been foreseen, and because of a toponymy issue. The two new regions interfere strongly with the numbering that what used to refer to the Chilean administrative units: since 2007, it is no longer possible to go on using the Roman numbers as before, since the new numbers do not fit the old north / south progression. Despite the very ordinary quality of the chosen names for the new territories, the introduction of a toponymy debate appears as the sign of a certain progress on the front of local democracy.